2022
DOI: 10.1002/agg2.20243
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction of soil health indicators to different regenerative farming practices on mineral soils

Abstract: Regenerative farming is a common practice adopted to enhance soil health. Routinely, cheaply measured soil health indicators can be used to predict unknown soil health indicators, which makes analysis simple and fast. The objective of this study was to determine the interaction and relationship between soil health indicators and the effects of regenerative farming practices on soil health indicators. We conducted a comprehensive on-farm study across Florida, measuring 11 soil health indicators for 592 soil sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(45 reference statements)
0
5
0
1
Order By: Relevance
“…This indicates cover crop mixed with organic amendments improves soil health compared with cover crop and organic amendment alone. Combination of organic amendments and cover cropping reported to be a viable option for Florida's growers to improve soil health (Xu et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates cover crop mixed with organic amendments improves soil health compared with cover crop and organic amendment alone. Combination of organic amendments and cover cropping reported to be a viable option for Florida's growers to improve soil health (Xu et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers (Manrique et al, 1991;Olorunfemi et al, 2016) reported that CEC was positively related to SOM and STC. Xu et al (2022) found that CEC was positively related to SOM, STN, and ACEP. The SOM acts as a negatively charge site which attracts cations, resulting in a strong correlation between CEC and SOM.…”
Section: Relationship Among Soil Propertiesmentioning
confidence: 92%
“…Soil pH was related to potential N mineralization (PNM) (Dessucault-Rompree et al, 2010) and phosphomoneesterase (PME) activity (Acosta-Martinez and Tabatabai, 2011). Xu et al (2022) found that soil pH was correlated to SOM, KMnO 4 -extractable C (POXC), autoclaved citrate-extractable protein (ACEP), soil total N (STN) and water holding capacity. Van Es and Karlen, (2019) observed that soil pH, P, and K concentrations were positively related to potential C mineralization (PCM).…”
Section: Introductionmentioning
confidence: 99%
“…Esas propiedades son los llamados indicadores, que incluyen los físicos, químicos y biológicos. Dentro de los primeros se incluyen al pH, la densidad aparente, la capacidad máxima de retención de agua, materia orgánica, carbón activo y capacidad de intercambio catiónico, micro y macro elementos; los cuales pueden actuar de manera independiente o pueden actuar entre ellos mejorando o suprimiendo la salud del suelo (Olorunfemi et al, 2016;Libohova et al, 2018;Xu et al, 2022).…”
Section: Contaminación De Los Suelosunclassified